PENGARUH FINANCIAL BEHAVIOR, SPIRITUAL QUOTIENT, EMOTIONAL QUOTIENT, FINANCIAL PLANNING, FINANCIAL INCLUSION TERHADAP FINANCIAL LITERATION DAN FINANCIAL QUOTIENT - ratnawati, tri; kartika, ika saridewi; rahmiyati, nekky (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2018)
ABSTRAKThe purpose of this research is to get empirical evidence about the influence of Financial Behavior, Spiritual Quotient, Emotional Quotient, Financial Planning, Financial Inclusion Against Financial Literation and Financial Quotient for Wives of Marine Soldiers at Base Defense Battalion V Surabaya. This research is focused on the wife of Marine Base Defense Battalion V Surabaya because it has a double role, the first role in supporting the duties and responsibilities of husbands who need full support from family, especially wife. Second, a wife hold the responsibility of managing family finances when the husband is on duty. In addition, they also serves as a housewife who experienced problems that are almost often faced by other housewives namely the problem of managing family cash flow, debt management and taking care of monthly investment. This research was conducted in Marine Base Defense Battalion V Surabaya and the number of samples used as many as 100 respondents. Sampling Technique in this research use Saturation Sampling technique that is sample determination technique when all member of population used as sample. Another term saturated sample is the census, where all members of the population are sampled. The research design used in this research is survey method. Data collection method used is questionnaire method. For this study data analysis using Partial Least Square (PLS) approach. PLS is an alternative approach that shifts from a Covarian-based SEM approach to a variance-based. SEM-based covariance generally test the causality / theory while PLS is more predictive model. The results showed that: (1) Financial Behavior has no significant effect on Financial Literation. (2) Financial Behavior has no significant effect on Financial Quotient. (3) Spiritual Quotient has significant effect on Financial Literation. (4) Spiritual Quotient has significant effect to Financial Quotient. (5) Emotional Quotient has significant effect to Financial Literation. (6) Emotional Quotient has significant effect to Financial Quotient. (7) Financial Planning has significant effect on Financial Literation. (8) Financial Planning has significant effect on Financial Quotient. (9) Financial Inclusion has significant effect on Financial Literation. (10) Financial Inclusion has significant effect on Financial Quotient. (11) Financial Literation has significant effect on Financial Quotient.Â Keywords : Financial Behavior, Spiritual Quotient, Emotional Quotient, Financial Planning, Financial Inclusion, Financial Literation, Financial Quotient.